Technology Meets Research:60 Years of CERN Technology: Selected Highlights - Thomas Taylor (Advanced Series on Directions in High Energy Physics, 2017)
"Big" science and advanced technology are known to cross-fertilize. This book emphasizes the interplay between particle physics and technology at CERN that has led to breakthroughs in both research and technology over the laboratory's first 60 years. The innovations, often the work of individuals or by small teams, are illustrated with highlights describing selected technologies from the domains of accelerators and detectors. The book also presents the framework and conditions prevailing at CERN that enabled spectacular advances in technology and contributed to propel the European organization into the league of leading research laboratories in the world. While the book is specifically aimed at providing information for the technically interested general public, more expert readers may also appreciate the broad variety of subjects presented. Ample references are given for those who wish to further explore a given topic.